The role of lipids in psoriasis - Anna Baran; Paulina Kiluk; Hanna Myśliwiec; Iwona Flisiak (Termedia Publishing House, 2017)
Psoriasis, affecting 2-4% of the world's population, is a chronic recurrent inflammatory skin disease. Its multifactorial aetiopathogenesis consists of, for example, abnormal epidermal proliferation, immune disturbances, and genetic, psychosomatic, environmental and hormonal factors. Psoriasis is also considered to be a systemic disorder closely associated with cardiovascular diseases, atherosclerosis, diabetes mellitus, obesity or metabolic syndrome. Lipids have a variety of biological functions. They participate not only in energy storage and expenditure or the formation of cell membranes, but also in inflammatory and metabolic signalling pathways. Disturbances in their homeostasis lead to the development of immunometabolic disorders, including psoriasis. Based on the available literature, this article presents selected molecular and clinical aspects involved in the multidirectional effect of lipids on psoriasis.